Proceso de ASC - APLICACION DE LOS ESTANDARES DE LA PRUEBA POR JUECES Y ARBITROS (2019)
This study explores the knowledge that both judges and arbitrators possess regarding the concept of the standard of proof and its application, as well as the lack of understanding of this concept when rendering judgment. While the concept is identified, there are conceptual gaps in its application, resulting in inadequate implementation. Additionally, it was observed that the applied standard sometimes becomes more stringent than what is established for certain processes. Furthermore, it has become evident that applying these standards makes it challenging to establish objective criteria.